Young at heart (1954) [videorecording (DVD)] - Douglas, Gordon, 1907-1993; Day, Doris, 1922-2019-; Sinatra, Frank, 1915-1998; Young, Gig, 1913-1978 (Artisan Entertainment, 2001)
A cynical hard-luck musician finds happiness and a new outlook when he falls in love with a small-town girl.